HQAM-OTFS: Enhancing the Shaping Gain of OTFS - Sangeeta N.; Sharma S.; Deka K.; Rajesh A. (My University, 2025)
Efficient data transmission is one of the most important features that any technology should possess. However, this efficiency should be achieved within the available resources, which in this context is energy. One method to achieve it is the use of hexagonal quadrature amplitude modulation (H-QAM). The recently proposed Orthogonal Time Frequency Space (OTFS) modulation is considered for high mobility communication scenarios over Orthogonal Frequency Division Multiplexing (OFDM) due to its unique multiplexing capabilities in the delay-Doppler (DD) domain. Nevertheless, there is still room for advancement in OTFS system design. In this paper, our objective is to enhance the coding gain and shaping gain of OTFS systems, which can complement the existing advantages of OTFS technology. To achieve this, we explore square quadrature amplitude modulation (S-QAM) and H-QAM models and calculate and compare their shaping and coding gains, supported by theoretical analysis. Our simulations demonstrate that H-QAM outperforms S-QAM, primarily because H-QAM provides greater tolerance to noise by expanding the Voronoi region. We analyze the impact of number of delay and Doppler bins on the performance of the OTFS for various modulation orders. Additionally we also find the closed form of bit error rate (BER) by considering the nature of the eigenvalues of the channel matrix. A comparison of peak-to-average power ratio (PAPR) is also done. © 2024 IEEE.